Unpacking barriers to socially inclusive weather index insurance: towards a framework for inclusion - Aheeyar, Mohamed M. M.; de Silva, Sanjiv; Senaratna Sellamuttu, Sonali; Arulingam, Indika (MDPI, 2019)
Floods account for a majority of disasters, especially in South Asia, where they affect 27 million people annually, causing economic losses of over US$1 billion. Climate change threatens to exacerbate these risks. Risk transfer mechanisms, such as weather index insurance (WII) may help buffer farmers against these hazards. However, WII programs struggle to attract the clients most in need of protection, including marginalized women and men. This risks re-enforcing existing inequalities and missing opportunities to promote pro-poor and gender-sensitive development. Key questions, therefore, include what factors constrain access to WIIs amongst heterogeneous communities, and how these can be addressed. This paper contributes to that end through primary data from two WII case studies (one in India, the other in Bangladesh) that identify contextual socio-economic and structural barriers to accessing WII, and strategies to overcome these. More significantly, this paper synthesizes the case study findings and those from a review of the literature on other WII initiatives into a framework to promote a systematic approach to address these challenges: an important step forward in moving from problem analysis to remedial action. The framework highlights actions across WII product design, implementation and post-implementation, to minimize risks of social exclusion in future WII schemes.